Linking Molecular Mechanisms and Evolutionary Consequences of Resource Polyphenism - Levis, Nicholas A.; Ragsdale, Erik J. (Frontiers in Integrative Neuroscience, 2022)
Resource polyphenism—the occurrence of environmentally induced, discrete, and intraspecific morphs showing differential niche use—is taxonomically widespread and fundamental to the evolution of ecological function where it has arisen. Despite longstanding appreciation for the ecological and evolutionary significance of resource polyphenism, only recently have its proximate mechanisms begun to be uncovered. Polyphenism switches, especially those influencing and influenced by trophic interactions, offer a route to integrating proximate and ultimate causation in studies of plasticity, and its potential influence on evolution more generally. Here, we use the major events in generalized polyphenic development as a scaffold for linking the molecular mechanisms of polyphenic switching with potential evolutionary outcomes of polyphenism and for discussing challenges and opportunities at each step in this process. Not only does the study of resource polyphenism uncover interesting details of discrete plasticity, it also illuminates and informs general principles at the intersection of development, ecology, and evolution.